The Effect of Social Media Marketing and E-WoM on Purchase Decisions for Cetaphil Skincare Products in Medan Mediated by Brand Trust - Kimberly Chow; Alfonsius (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
Over the past few years, skincare has evolved into a crucial part of the daily routines of a large number of individuals all over the world. The skincare market in Indonesia is expanding at a quick rate, and there is a wide variety of goods accessible, ranging from locally produced brands that are affordable to international brands. This study aims to analyze the effect of social media marketing and Electronic Word of Mouth (E-WoM) on purchase decisions for Cetaphil skincare products in Medan, with brand trust as a mediating variable. The research utilizes a quantitative approach. Data were collected through questionnaires distributed to 140 respondents who have interacted with Cetaphil’s online content or made a purchase. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that both E-WoM have a significant positive effect on brand trust and purchase decision, while social media marketing shows no significant effect toward brand trust and purchase decision. Furthermore, brand trust plays a partial mediating role in the relationship between the independent variables of E-WoM toward purchase decisions.